Affective Valence and Enjoyment in High- and Moderate-High Intensity Interval Exercise. The Tromsø Exercise Enjoyment Study - Hammer, Tord Markussen; Pedersen, Sigurd; Pettersen, Svein Arne; Rognmo, Kamilla; Sagelv, Edvard H. (Frontiers in Psychology, 2022)
Introduction: Exercise at high intensity may cause lower affective responses towards exercise compared with moderate intensity exercise. We aimed to elucidate affective valence and enjoyment in high- and moderate-high interval exercise. Methods: Twenty recreationally active participants (9 females, 11 males, age range: 20-51 years) underwent three different treadmill running exercise sessions per week over a three-week period, in randomized order; 1) CE70: 45 minutes continuous exercise at 70% of heart rate maximum (HRmax), 2) INT80: 4x4 minutes intervals at 80% of HRmax, 3) INT90: 4x4 minutes intervals at 90% of HRmax. Pre-tests included graded submaximal steady state intensities and a test to exhaustion for determining peak oxygen uptake and HRmax. Affective valence (pleasure/displeasure) was measured before, during and after the sessions using the Feeling Scale (FS). Enjoyment was assessed before and after the sessions applying the Physical Activity Enjoyment Scale (PACES) and during the sessions using the Exercise Enjoyment Scale (EES). Results: The participants felt lower pleasure (between-sessions effect: p=0.02, pη2: 0.13) during INT90 sessions (FS: 1.08, 95% CI: 0.35-1.92) compared with INT80 (FS: 2.35, 95% CI: 1.62-3.08, p=0.052) and CE70 sessions (FS: 2.45, 95% CI: 1.72-3.18, p=0.03), with no differences between INT80 and CE70 sessions (p=1.00). There were higher enjoyment after INT80 sessions (PACES: 101.5, 95% CI: 95.7-107.3) versus CE70 sessions (PACES: 91.3 95% CI: 85.5-97.1, p=0.046), and no differences between INT90 (PACES: 98.2, 95% CI: 92.4-103.4) and CE70 (p=0.29) or INT80 (p=1.00). For enjoyment during exercise CE70 were perceived more enjoyable, and INT80 and INT90 less enjoyable in week 2 (EES: week x session: p=0.01, pη2: 0.11; CE70: 4.3, 95% CI: 3.6-4.9, INT80: 4.6, 95% CI: 3.9-5.2, INT90: 4.0, 95% CI: 3.4-4.7) and 3 (EES: CE70: 4.2, 95% CI: 3.7-4.8, INT80: 4.8, 95% CI: 4.2-5.3, INT90: 4.3, 95% CI: 3.8-4.9) than in week 1 (EES: CE70: 3.5, 95% CI: 3.0-4.0, INT80: 5.0, 95% CI: 4.5-5.5, INT90: 4.5, 95% CI: 4.0-5.0). Conclusion: The negative affective consequences associated with high intensity interval exercise can be alleviated by keeping the intensity at or around 80% of HRmax while preserving the beneficial enjoyment responses associated with high intensity interval exercise.